High-Speed THz Time-of-Flight Imaging with Reflective Optics - Yoo, Hoseong; Kim, Jangsun; Ahn, Yeong Hwan (Sensors, 2023)
In this study, we develop a 3D THz time-of-flight (TOF) imaging technique by using reflective optics to preserve the high-frequency components from a THz antenna. We use an Fe:InGaAs/InAlAs emitter containing relatively high-frequency components. THz-TOF imaging with asynchronous optical sampling (ASOPS) enables the rapid scanning of 100 Hz/scan with a time delay span of 100 ps. We characterize the transverse resolution using knife edge tests for a focal length of 5; the Rayleigh resolution has been measured at 1.0 mm at the focal plane. Conversely, the longitudinal resolution is determined by the temporal pulse width, confirmed with various gap structures enclosed by a quartz substrate. The phase analysis reveals that reflected waves from the top interface exhibit a phase shift when the gap is filled by high-indexed materials such as water but shows in-phase behavior when it is filled with air and low-indexed material. Our imaging tool was effective for inspecting the packaged chip with high lateral and longitudinal resolution. Importantly, the phase information in 2D and 3D images is shown to be a powerful tool in identifying the defect—in particular, delamination in the chip—which tends to be detrimental to the packaged chip’s stability.
Keywords: High frequency components; High Speed; Higher-frequency components; Longitudinal resolution; Packaged chips; Reflective optics; Terahertz imaging; THz antenna; Time-of flight; Time-of-flight imaging; Imaging, Three-Dimensional; Optics and Photonics; Water; nondestructive testing; terahertz imaging; time-of-flight